Evaluation of the Importance of Yam Cossettes Flour Couscous (wassa-wassa tchigan) in the Diabetics Diet in Benin - BEHANZIN, G. Justin; Chabi, B. Christophe; CHABI, NICODÈME WOROU; OGBON, E. Azaratou; KONFO, Christian T. R.; AHISSOU, HYACINTHE (My University, 2018)
The measurement of food glycemic index constitutes a considerable advance in medicine because it makes it possible to orient the choice of foods according to the health of a patient. This study aims to improve the diet of diabetics in Benin. It consisted in the determination of the total sugar content and the glycemic index of the yam chips flour couscous (wassa-wassa tchigan) and then the evaluation of the influence of this food on the glycemic index of the subjects. This cross-sectional study covered 7 apparently healthy subjects. In the first test each subject consumed a dish of wassa-wassa tchigan containing 50g of carbohydrate. Each subject was tested twice for a period of one week. A week later, in the second test, bread crumb containing 50 g of carbohydrate was ingested. Each glycemic test was measured at regular intervals of 30 minutes for 3 hours. The study on the determination of the total sugar content of wassa-wassa tchigan revealed that one gram (1 g) of wassa-wassa tchigan contained 483.55mg of carbohydrate. The peak of blood glucose increase in subjects was reached from the thirtieth minute postprandial. The area under the curve of the subjects varied from the reference food to the test food and from one subject to another. The glycemic index of the wassa-wassa tchigan determined was 36.83% which made this meal a meal with very low glycemic index.
Keywords: yam cossettes flour couscous (wassa-wassa); soft bread; glycemic index